Cigarette smoking reduces deep retinal vascular density. (13th April 2020) - Dogan, Mustafa; Akdogan, Muberra; Gulyesil, Furkan Fatih; Sabaner, Mehmet Cem; Gobeka, Hamidu Hamisi
Abstract : Background: The purpose of this study was to report the effects of smoking on retinal vascular parameters. Methods: In this cross‐sectional study design, 24 smokers were included as a study group and 26 age‐ and sex‐matched non‐smokers as a control group. A detailed ophthalmic examination including review of medical history, visual acuity testing, intraocular pressure measurement by Goldmann applanation tonometry, ocular movement and pupillary reflex examination, slitlamp biomicroscopy as well as dilated funduscopic examination were undertaken in all participants. Participants underwent optical coherence tomography angiography (OCT‐A) scanning with RTVue XR Avanti AngioVue OCT‐A (Optovue, Fremont, CA, USA) as well as the measurement of axial length using an AL Scan (Nidek Co., Ltd., Gamagori, Japan). Results: The study comprised of 18 men and six women with a mean age of 28.1 ± 4.8 years in the study group and 19 men and seven women with a mean age of 27.4 ± 2.7 years in the control group. The mean exposure to cigarette smoking was 3.3 ± 1.0 pack‐years. Total vascular density, parafoveal vascular density and perifoveal vascular density in the deep capillary plexus observed with OCT‐A were significantly lower in the smoking group compared to the control group (p = 0.02, 0.01 and 0.01, respectively). Conclusion: Retinal vascular changes caused by cigarette smoking may occur even at low pack‐year exposure. These changes, which can be demonstrated by OCT‐A, may reflect the early impact of cigarette smoking on the microvascular system.